963 THE IMPACT OF AGE, SEX AND MORBIDITY COUNT ON EARLY TERMINATION: A META-ANALYSIS OF INDIVIDUAL PATIENT DATA FROM CLINICAL TRIALS. (14th June 2022) - Lees, J S; Hanlon, P; Butterly, E; Wild, S H; Mair, F S; Taylor, R S; Guthrie, B; Gillies, K; Dias, S; Welton, N; McAllister, D A
Abstract: Introduction: Multimorbidity is found in around half of people with any long-term condition but is substantially less common in randomised controlled trials ('trials'). Multimorbidity may diminish a participant's ability to complete a trial. However, empirical estimates of the association between individual patient characteristics and early termination are lacking. Method: Individual patient-level data were obtained from Phase 3/4 trials contained within two clinical trial repositories. Eligible trials for inclusion were identified according to pre-specified criteria (PROSPERO CRD42018048202). Within each trial, the association between morbidity count and early termination (failure for any reason to complete the final trial visit) was estimated in logistic regression models, adjusting for age and sex. These estimates were meta-analysed in Bayesian linear models, with partial pooling across index conditions and drug classes. Using these estimates, the impact of morbidity count on early termination was modelled for a set of notional trials. Results: In 92 trials across 20 index conditions and 17 drug classes, the mean morbidity count ranged from 0.3–2.7. Neither age nor sex was associated with early termination (OR 1.04, 95% CI 0.98–1.11; OR 1.00, 95% PI 0.95–1.07 respectively). Morbidity count was associated with early termination (OR per additional morbidity: 1.11, 95% CI: 1.07 to 1.14). There was no evidence of non-linearity in the association between morbidity count and early termination, and there was minimal variation across drug classes and index conditions. For a notional trial with high level of early termination in individuals without multimorbidity, doubling the mean morbidity count from 1 to 2 increases risk of early termination from 29% to 31%. Conclusion: Multimorbidity, irrespective of age and sex, is associated with a relatively modest increased odds of early termination of trial participation. The benefit of increased generalisability of trials by including patients with multimorbidity appears likely to outweigh the disadvantages of lower retention.